THE OCCUR DEGREE OF THE BRONCHOOBSTRUCTIVE SYNDROME’S DEPENDENCE TO THE HUE OF THE REFLUXATE IN THE GASTROESOPHAGEAL REFLUX DISEASE - Yuldasheva D. H. (Galaxy International Interdisciplinary Research Journal, 2024)
The urgency of the problem. Nowadays, gastroesophageal reflux disease (GERD) holds the high positions according to happening index among the gastroenterological diseases. The diagnosing disease, almost is not difficult, because typical clinical symptoms of the GERD observed frequently in the clinical practice, for example heartburn, burp, regurgitating and others. However, typical forms of the disease are diagnosed much difficulty. Because clinical view of them looks like the diseases of the neighbor organs [1,2,4,6,7]. The broncho-pulmonary form of the GERD from atypical views is much observed. For instance, according to medical literatures one of atypical forms of the GERD reflux –asthma from 30 % until 90 % happens together with bronchial asthma (BA) [2,3,5,8,9]. According to our primary researchings among the atypical forms of the GERD, precisely, broncho-pulmonary type is progressive because we aimed during the research to define the immixture of register grade of the bronchoobstructive syndrome (BOS) with hue of the refluxate.